The Influence of Product Innovation and Marketing Strategy on the Competitiveness of MSMEs - Wartini, Sri; Suseno, Dewi Alima Nostalia (Nomico, 2026)
This study aims to analyze the effect of product innovation and marketing strategy on the competitiveness of MSMEs in Indonesia, both partially and simultaneously. A causal quantitative approach was employed, with data collected through an online questionnaire distributed via Google Form to 100 MSME owners selected using purposive sampling. The research instruments were developed using a five-point Likert scale based on Gunday et al. (2011) for product innovation (10 items), Kotler & Keller (2016) for marketing strategy (12 items), and Porter (1990) for MSME competitiveness (10 items). Following validity and reliability testing, data were analyzed using multiple linear regression with R statistical software. The results indicate that: (1) product innovation has a positive and significant effect on MSME competitiveness (β = 0.351; t = 4.807; p < 0.001); (2) marketing strategy has a positive and significant effect on MSME competitiveness (β = 0.538; t = 7.368; p < 0.001); and (3) simultaneously, product innovation and marketing strategy significantly affect MSME competitiveness with F = 58.200 (p < 0.001) and R² = 0.545, indicating that both variables explain 54.5% of the variation in MSME competitiveness. These findings imply that MSMEs in Indonesia need to synergistically integrate product innovation capabilities and digital marketing strategies to achieve sustainable competitiveness.